Multitemporal study on forest fragmentation in sierra Fria, Aguascalientes, Mexico - Chapa Bezanilla, Daniel; Sosa Ramírez, Joaquín; de Alba Ávila, Abraham (Instituto de Ecología, A.C., 2016)
The Sierra Fría in Aguascalientes is part of the Sierra Madre Occidental Physiographic Province. The predominant vegetation types in the area are pine (P i n u s spp.), oak (Q u e r c u s s p p . ) , juniper (J u n i p e r u s spp.) and mixed forests that have been modified due to wood extraction, fire and heavy grazing. In order to estimate the degree of deterioration or recuperation of these forests a multitemporal study was done from the comparative analyses of airphotos of the area for 1956, 1970 and 1993, that were digitized and georeferenced. Changes in the areas occupied by different types of forest were compared the degree of site fragmentation of each vegetation type, using functions from the geographical information systems. Photographic mosaics for each date were generated, processed and analyzed. The area occupied by each of the forest types in the three dates was compared and an increase was found for Juniper forest, for pine forests and for oak forests from 1956 to 1993. At the same time, oaks increased in number of sites, as will as pine and juniper. Due to these results it was considered that the changes in area and fragmentation degree were not significant which indicates that the rate of use of these resources is about equal to the rate of recuperation. Nonetheless, notable changes were observed in the cover degree or micro fragmentation within sites of each vegetation type, with a tendency to increase.